Two-component polyurethane-based thermally conductive adhesive composition, polyurethane-based thermally conductive adhesive and article thereof
By using two-component polyol urea thermal conductivity adhesive in complex applications such as electric vehicles, the problem of degradation of adhesive force and mechanical properties when thermal conductivity is improved in the prior art is solved, and high thermal conductivity and good adhesive properties are achieved, ensuring the safety and long life of energy storage equipment.
Patent Information
- Application Number
- JP2024556196
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-03-23
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2042-03-23
AI Technical Summary
The prior art often impairs adhesion and mechanical properties when improving thermal conductivity, especially when bonding surfaces with low surface energy with surfaces with high surface energy, the adhesion performance is insufficient and it is difficult to meet the needs of complex applications such as electric vehicles.
A two-component polyol urea thermally conductive adhesive is used, which consists of polyol urea containing thermal filler. Through specific formula ratios and reaction conditions, the adhesive finds a balance between high thermal conductivity and good adhesion.
It achieves a balance between high thermal conductivity and good mechanical and adhesive properties, and is especially suitable for complex applications such as electric vehicles, ensuring the safety and long life of energy storage equipment.
Smart Images

Figure 2025509994000001 
Figure 2025509994000002 
Figure 2025509994000003
Abstract
Description
[Technical field]
[0001] Technical Field The present invention relates to a two-part polyurethane-based thermally conductive adhesive composition, a polyurethane-based thermally conductive adhesive, and an article comprising the polyurethane-based thermally conductive adhesive. [Background technology]
[0002] 2. Background of the Invention Thermally conductive adhesives are used in several applications where components need to be fixed to a structure and where heat needs to be dissipated from the components, thus finding many applications in the electronics sector where excess thermal energy generated by electronic components needs to be dissipated.
[0003] Developments in the field of electromobility, especially the adoption of electric vehicles such as cars and trucks, have shown that materials that meet complex requirements are needed. Fixing energy storage devices in particular has proven to be challenging, and any adhesives used must exhibit thermal conductivity to deflect any heat generated, for example during charging of the energy storage device, while at the same time possessing mechanical and adhesive properties that allow for a safe and long-lasting assembly. Furthermore, the adhesives used must have good adhesion properties between surfaces with different surface energy values.
[0004] In general, increased thermal conductivity has a detrimental effect on mechanical properties, especially on the adhesion between two substrates with dissimilar properties, for example a low surface energy surface and a high surface energy surface. Summary of the Invention
[0005] Summary of the Invention It is therefore an object of the present invention to overcome the above mentioned drawbacks by providing an adhesive composition which advantageously combines good adhesive properties with good thermal conductivity, which adhesive composition is suitable for use in electric vehicles for bonding between two substrates with different properties.
[0006] It has been unexpectedly found that this object is achieved by a polyurethane-based thermally conductive adhesive comprising a cured product obtained from a two-part polyurethane-based thermally conductive adhesive composition. The two-part polyurethane-based thermally conductive adhesive composition comprises at least a thermally conductive filler, a polyhydroxy compound, a crosslinking agent, a special (poly)isocyanate prepolymer, and an isocyanate-containing compound.
[0007] In one embodiment, the present invention provides a method for producing a polyhydroxyl-terminated polybutadiene comprising: component (A) comprising a polyhydroxy compound and a crosslinking agent, wherein the polyhydroxy compound comprises a polyether polyol having a weight average molecular weight of 300-1200 and a hydroxy functionality of 2; component (B) comprising an isocyanate-containing compound and a (poly)isocyanate prepolymer having active isocyanate groups prepared by reacting a hydroxyl-terminated polybutadiene with an excess of an aromatic isocyanate, wherein the molar ratio of the OH groups of the hydroxyl-terminated polybutadiene to the NCO groups of the aromatic isocyanate is ( The present invention provides a two-component polyurethane-based thermally conductive adhesive composition comprising a (poly)isocyanate prepolymer having a formula of 0.23 to 0.32, wherein component (A) and / or component (B) contain a thermally conductive filler, the content of the thermally conductive filler being 82.5 to 85.0 wt % based on the total amount of the adhesive composition, and components (B) and (A) are present in a ratio of NCO groups of the isocyanate-containing compound and (poly)isocyanate prepolymer to OH groups of the polyhydroxy compound of 0.8 to 1.6.
[0008] In another aspect, the present invention also provides a polyurethane-based thermally conductive adhesive which is a cured product of the two-component polyurethane-based thermally conductive adhesive composition.
[0009] Third, the present invention also relates to articles, particularly electric vehicles, that include the polyurethane-based thermally conductive adhesive.
[0010] Fourthly, the present invention also provides the use of the cured product of the two-part polyurethane-based thermally conductive adhesive composition as a thermally conductive adhesive for bonding substrates, particularly in the manufacture of batteries in the automotive industry. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Detailed Description of the Invention In the following text, the present invention will be described in more detail. Each aspect thus described may be combined with any other aspect or aspects, unless expressly stated to be incompatible. In particular, any feature indicated as being preferred or advantageous may be combined with any other feature or features indicated as being preferred or advantageous.
[0012] In the context of the present invention, the terms used shall be construed in accordance with the following definitions, unless the context indicates otherwise.
[0013] As used herein, the singular forms "a," "an," and "the" include both singular and plural references unless the context clearly dictates otherwise. As used in this specification and the appended claims, the term "or" is generally used in its sense including "and / or" unless the content clearly dictates otherwise.
[0014] As used herein, the terms "comprising," "comprises," and "comprised of" are synonymous with, and are inclusive or open ended, and do not exclude additional, unrecited components, elements, or steps.
[0015] The recitation of numerical endpoints includes the respective ranges, as well as all values and fractions subsumed within the recited endpoints.
[0016] Unless otherwise defined, all terms used in disclosing the present invention, including technical and scientific terms, have the meanings commonly understood by those of ordinary skill in the art. As a further guide, definitions of terms are included to better understand the teachings of the present invention.
[0017] In the context of this disclosure, a number of terms are used.
[0018] Thermal conductivity is measured according to ISO 22007-2:2015 (hot disk).
[0019] As used herein, "Mw" means weight average molecular weight, also referred to as theoretical, as determined by gel permeation chromatography (GPC) against linear polystyrene standards of 1.1 M to 580 Da, which may be performed using a Waters 2695 Separation Module equipped with a Waters 2414 differential refractometer (RI detector). "Mn" means number average molecular weight, also referred to as theoretical, as determined by gel permeation chromatography (GPC).
[0020] The term "cure" refers to any form of radiation, heating, or physical or chemical reaction that results in hardening or an increase in viscosity.
[0021] Ingredient A Component A of the two-part polyurethane-based thermally conductive adhesive composition of the present invention comprises a polyhydroxy compound having a specific molecular weight and a specific hydroxy functionality, and a crosslinker having a specific molecular weight.
[0022] <Polyhydroxy compounds> In some preferred embodiments of the present invention, the polyhydroxy compound is a polyol having a molecular weight Mw of 300 to 1,200 g / mol, in particular 400 to 1,000 g / mol. And the hydroxy functionality of the polyol is 2. More preferably, the polyhydroxy compound contains secondary hydroxyl groups. More preferably, the polyol is a polyether polyol, preferably a polyether diol containing primary hydroxyl groups or a mixture of primary and secondary hydroxyl groups. Examples of suitable polyether polyols are polyoxyalkylene polyols such as polyethylene glycol, polypropylene glycol, polytetramethyl glycol and polybutyl glycol. Also suitable for the purposes of the present invention are homopolymers or copolymers of the listed polyoxyalkylene polyols, as well as mixtures thereof. Particularly suitable copolymers are those comprising an adduct of a compound selected from the group consisting of ethylene glycol, propylene glycol, diethylene glycol, propylene glycol, triethylene glycol, 2-ethylhexanediol-1,3-glycerin, trimethylolpropane, trimethylolethane, tris(hydroxyphenyl)propane, triethanolamine and triisopropylamine with at least one compound selected from the group consisting of ethylene oxide, propylene oxide and butylene oxide.
[0023] In some preferred embodiments, the polyhydroxy compound is propylene glycol end-capped polypropylene glycol or ethylene glycol end-capped polyethylene glycol.
[0024] In some preferred embodiments, the polyhydroxy compound is selected from the group consisting of amorphous, partially crystalline polyester polyols that are liquid at a temperature of 25°C.
[0025] Examples of commercially available polyols include, for example, DESMOPHEN 1262 BD from Covestro, or VORANOL WD 2104 Polyol from Dow.
[0026] In some preferred embodiments of the present invention, components A and B are present in the composition at a molar ratio of NCO / OH (molar ratio of NCO groups on the free isocyanate-containing compound and the (poly)isocyanate prepolymer to hydroxyl groups on the polyol) of 0.8, or 0.82, or 0.85, or 0.88, or 0.9, or 1.0, or 1.1 at a lower limit and a molar ratio of NCO / OH of 1.6, or 1.52, or 1.5, or 1.44, or 1.4, or 1.35, or 1.3, or 1.28, or 1.24, or 1.2, or 1.15 at an upper limit. In some preferred embodiments of the present invention, components A and B are present in the composition at a molar ratio of NCO / OH of 0.8 to 1.6, or 0.9 to 1.2 when the volume ratio of A / B is 1:1. It has surprisingly been found that the adhesive properties of the thermally conductive adhesive composition can be improved if the amount of polyol is within the claimed range.
[0027] The thermally conductive adhesive composition of the present invention unexpectedly exhibits a desirable combination of properties, particularly high thermal conductivity combined with excellent mechanical and adhesive properties.
[0028] <Crosslinking agent> Component A includes a crosslinker. Typically, a crosslinker is a low molecular weight molecule used to link polymers to form a network structure. In some embodiments, a suitable crosslinker is a low molecular weight molecule with a hydroxy functionality of 3. In some preferred embodiments, the crosslinker is selected from the group consisting of triol polyether polyols, triol polyester polyols, and mixtures thereof.
[0029] In some preferred embodiments, the crosslinker is present in Component A in an amount of at least 0.1 wt%, or in an amount of 2-4.5 wt%, or in an amount of 2.5-4 wt%, based on the total weight of the two-part polyurethane-based thermally conductive adhesive composition. It has been found that the mechanical properties of the thermally conductive adhesive composition of the present invention can be tailored as desired by varying the amount of crosslinker in Component A.
[0030] An example of a commercially available crosslinker is, for example, VORANOL CP 450 Polyol from Dow.
[0031] <Thermal conductive filler> In some embodiments, a thermally conductive filler may be present in the adhesive composition (or in either or both of Component A and Component B).
[0032] In a preferred embodiment, the thermally conductive filler is selected from the group consisting of metal oxides, non-metal oxides, metal nitrides, non-metal nitrides, metal hydroxides, metal silicates, metal sulfides, and combinations thereof.
[0033] Suitable metal oxides for use as thermally conductive fillers are preferably selected from oxides of metals selected from the group consisting of oxides of tin, indium, antimony, aluminum, titanium, iron, magnesium, zinc, rare earth metals, alkali metals, Mg, Ca, Sr and Ba, mixed metal oxides and mixtures thereof.
[0034] Suitable non-metal oxides for use as thermally conductive fillers are preferably selected from oxides of silicon.
[0035] Suitable metal nitrides for use as thermally conductive fillers are preferably selected from nitrides of aluminium.
[0036] Suitable non-metallic nitrides for use as thermally conductive fillers are preferably selected from nitrides of boron, silicon, mixed non-metallic nitrides and mixtures thereof.
[0037] Suitable metal hydroxides for use as thermally conductive fillers are preferably selected from the hydroxides of metals selected from the group consisting of hydroxides of tin, indium, antimony, aluminum, titanium, iron, magnesium, zinc, rare earth metals, alkali metals, Mg, Ca, Sr and Ba, mixed metal hydroxides and mixtures thereof.
[0038] Suitable metal silicates for use as thermally conductive fillers are preferably selected from the group consisting of silicates of metals selected from the group consisting of silicates of tin, indium, antimony, aluminum, titanium, iron, magnesium, zinc, rare earth metals, alkali metals, Mg, Ca, Sr and Ba, mixed metal silicates and mixtures thereof.
[0039] Suitable metal sulfides for use as thermally conductive fillers are preferably selected from sulfides of metals selected from the group consisting of sulfides of tin, indium, antimony, aluminum, titanium, iron, magnesium, zinc, rare earth metals, alkali metals, Mg, Ca, Sr and Ba, mixed metal sulfides and mixtures thereof.
[0040] To tailor the properties of the filler, especially its thermal conductivity and dispersibility, the materials used can be surface modified.
[0041] Examples of commercially available conductive fillers are, for example, QYH40 and QY5-1 from Suzhou Ginet New Material Technology Co. Ltd., MARTINA ON-908 from JM Huber Corporation, FA-051 from Foshan Jinge Material Co. Ltd., BAK-40, BAK-5, NSM-2 from Ya'an Bestry Performance Materials Co., Ltd.
[0042] In some embodiments, the thermally conductive filler is present in component A and / or component B of the two-part polyurethane-based thermally conductive adhesive composition. Based on the total weight of the two-part polyurethane-based thermally conductive adhesive composition, the lower limit of the thermally conductive filler is 82.5 wt%, or 82.85 wt%, or 82.9 wt%, or 83.0 wt%, or 83.11 wt%, or 83.39 wt%, or 83.54 wt%; the upper limit of the thermally conductive filler is 85.0 wt%, or 84.1 wt%, or 84.06 wt%, or 83.71 wt%. In some preferred embodiments, the thermally conductive filler is present in component A and / or component B of the two-part polyurethane-based thermally conductive adhesive composition in an amount of 82.5 to 85.0 wt%, preferably 82.8 to 84.1 wt%, based on the total weight of the two-part polyurethane-based thermally conductive adhesive composition.
[0043] It has been surprisingly found that the amount of thermally conductive filler within the above ranges can improve the thermal conductivity of the thermally conductive adhesive composition without substantially affecting the adhesive properties. The cured polyurethane-based adhesive exhibits a thermal conductivity of at least 1.98 W / (m·K), or at least 1.99 W / (m·K), or at least 2.00 W / (m·K), or at least 2.03 W / (m·K), or at least 2.10 W / (m·K), or at least 2.13 W / (m·K), or at least 2.20 W / (m·K), or at least 2.24 W / (m·K), or at least 2.40 W / (m·K), or at least 2.48 W / (m·K), or at least 2.50 W / (m·K), as measured by ISO 22007-2-2015.
[0044] Component B Component B of the two-part polyurethane-based thermally conductive adhesive composition of the present invention comprises an isocyanate-containing compound, a (poly)isocyanate prepolymer. In some embodiments of the present invention, component B comprises a mixture of an aromatic NCO-terminated compound, a (poly)isocyanate prepolymer and a thermally conductive filler.
[0045] <(Poly)isocyanate prepolymer> In some embodiments, the (poly)isocyanate prepolymer is the reaction product of a hydroxyl-terminated polybutadiene with an excess of an isocyanate. A more preferred (poly)isocyanate prepolymer can be obtained, for example, by reacting a polybutadiene diol with an excess of an aromatic isocyanate.
[0046] Such isocyanates are selected from the group consisting of 1,5-naphthylene diisocyanate (NDI), 2,4'- or 4,4'-diphenylmethane diisocyanate (MDI), isomers of toluylene diisocyanate (TDI), methylene triphenyl triisocyanate (MIT), hydrated MDI (H12MDI), tetramethylxylylene diisocyanate (TMXDI), 1-isocyanatomethyl-3-isocyanato-1,5,5-trimethylcyclohexane (IPDI), xylylene diisocyanate (XDI), pentamethylene diisocyanate, dicyclohexylmethane diisocyanate, and dimers, trimers, oligomers and polymers thereof.
[0047] The hydroxyl-terminated polybutadiene having a polybutadiene structure may have a 1,2-vinyl structure or a 1,4-trans structure alone, or a mixture of the 1,2-vinyl structure and the 1,4-trans structure, or the 1,2-vinyl structure, the 1,4-trans structure and the 1,4-cis structure, or the 1,4-trans structure and the 1,4-cis structure.
[0048] In some embodiments of the present invention, the hydroxyl terminated polybutadiene is a linear, non-hydrogenated, hydroxyl terminated polybutadiene that is liquid at 25°C.
[0049] In some embodiments of the invention, the hydroxyl terminated polybutadiene is a polybutadiene diol having terminal hydroxyl groups and a number average molecular weight (Mn) in the range of 1,000 to 5,000 g / mol, or 1,200 to 4,500 g / mol, or 2,000 to 3,000 g / mol, and / or an average hydroxyl (OH) functionality in the range of 1.7 to 3.5, or 1.9 to 2.6, or 2.2 to 2.5.
[0050] In some embodiments of the invention, the hydroxyl-terminated polybutadiene and excess isocyanate are reacted at an OH:NCO molar ratio (the molar ratio of hydroxyl groups on the hydroxyl-terminated polybutadiene to NCO groups on the aromatic isocyanate in the (poly)isocyanate prepolymer formula) of 0.23 to 0.32, preferably 0.235 to 0.261.
[0051] In some embodiments, the lower limit of the (poly)isocyanate prepolymer is 6.5 wt%, or 7.0 wt%, or 7.09 wt%, or 7.5 wt%, or 7.51 wt%, or 7.89 wt%, or 8.24 wt%, based on the total weight of the two-part polyurethane-based thermally conductive adhesive composition; the upper limit of the thermally conductive filler is 10.00 wt%, or 9.90 wt%, or 9.50 wt%, or 9.37 wt%. In some embodiments, the (poly)isocyanate prepolymer is present in the two-part polyurethane-based thermally conductive adhesive composition in an amount of 6.63 to 10.00 wt%, or 6.63 to 8.24 wt%, based on the total weight of the two-part polyurethane-based thermally conductive adhesive composition.
[0052] In some embodiments, the lower limit of the weight ratio of the hydroxyl-terminated polybutadiene is 3.00 wt%, or 3.10 wt%, or 3.20 wt%, or 3.29 wt%, or 3.31 wt%, or 3.54 wt%, or 3.65 wt%, based on the total weight of the two-part polyurethane-based thermally conductive adhesive composition; the upper limit of the hydroxyl-terminated polybutadiene in the adhesive composition is 5.50 wt%, or 5.40 wt%, or 5.10 wt%, or 4.70 wt%, or 4.12 wt%, or 4.02 wt%, or 3.95 wt%. In some embodiments, the hydroxyl-terminated polybutadiene is reacted with an accessible amount of aromatic isocyanate in an amount of 3.00 to 5.50 wt%, or 3.20 to 4.70 wt%, or 3.29 to 4.69 wt%, based on the total weight of the two-part polyurethane-based thermally conductive adhesive composition.
[0053] It has surprisingly been found that thermally conductive adhesive compositions, by using the claimed (poly)isocyanate prepolymers, exhibit a combination of desirable properties, in particular high thermal conductivity combined with excellent adhesive properties.
[0054] <Isocyanate-containing compounds> In some preferred embodiments, the isocyanate-containing compound is selected from the group consisting of 1,5-naphthylene diisocyanate (NDI), 2,4'- or 4,4'-diphenylmethane diisocyanate (MDI), isomers of toluylene diisocyanate (TDI), methylene triphenyl triisocyanate (MIT), hydrated MDI (H12MDI), tetramethyl xylylene diisocyanate (TMXDI), 1-isocyanatomethyl-3-isocyanato-1,5,5-trimethylcyclohexane (IPDI), xylylene diisocyanate (XDI), hexane-1,6-diisocyanate (HDI), pentamethylene diisocyanate, dicyclohexylmethane diisocyanate, and dimers, trimers, oligomers, and polymers thereof.
[0055] In some particularly preferred embodiments, the isocyanate-containing compound comprises an aromatic NCO-terminated compound.
[0056] It should be understood that isocyanate-containing compounds include unreacted free aromatic isocyanates from the excess isocyanate in the (poly)isocyanate prepolymer preparation.
[0057] In some preferred embodiments, the isocyanate-containing compound is a mixture of MDI isomers.
[0058] Examples of commercially available isocyanate-containing compounds include, for example, DESMODUR CD-C from Covestro and WANNATE CDMDI-100L from Wanhua Chemical.
[0059] In some embodiments, the isocyanate-containing compound is present in the two-part polyurethane-based thermally conductive adhesive composition in an amount of at least 1 wt%, alternatively in an amount of 1.0 to 1.8 wt%, or 1.2 to 1.6 wt%, based on the total weight of the two-part polyurethane-based thermally conductive adhesive composition.
[0060] <Additives> Apart from the thermal conductivity, mechanical and adhesive properties of the adhesive composition, other properties such as processability must also be considered. In particular, the curability and viscosity of the thermally conductive adhesive composition must be adapted to the respective application. The composition according to the invention may further comprise additives. These optional additives may be used to affect the properties of the composition, such as processability, flame retardancy and water removability. Preferably, the one or more additives are selected from the group consisting of additional fillers, pigments, rheology modifiers, drying agents, plasticizers, flame retardants, surfactants, defoamers, dispersants, thixotropic agents.
[0061] In a preferred embodiment, the amount of additive present in the thermally conductive adhesive composition is from 0.01 to 5.0% by weight, preferably from 0.1 to 3.3% by weight, based on the total weight of the thermally conductive adhesive composition.
[0062] <Adhesive composition> It has been unexpectedly found that the mechanical and adhesive properties of the adhesive composition of the present invention are advantageously balanced when the mixing ratio of component A to component B is within a certain range. Accordingly, a preferred embodiment of the present invention is one in which the mixing volume ratio of component A to component B is 0.9:1 to 1.1:1, preferably 1:1.
[0063] In order to be processable in industrial applications, the thermally conductive adhesive composition must have a viscosity that allows easy and accurate application. Thus, in some embodiments, the adhesive composition according to the present invention preferably has a viscosity of 1500 Pa·s or less, preferably 1000 Pa·s or less, particularly 30 to 800 Pa·s, or 300 to 700 Pa·s, measured at 25°C (1 s according to ASTM D2196-2015). -1 (Tested by Anton Paar Rheometer using PP25 spindle at shear rate of 1000 rpm).
[0064] The thermally conductive adhesive composition of the present invention is thermally conductive. In some preferred embodiments, the cured polyurethane adhesive exhibits a thermal conductivity of at least 1.98 W / (m·K), or at least 1.99 W / (m·K), or at least 2.0 W / (m·K), or at least 2.1 W / (m·K), or at least 2.2 W / (m·K), or at least 2.48 W / (m·K), or at least 2.50 W / (m·K), as measured by ISO 22007-2-2015. It has been unexpectedly found that by selecting the formulation of the thermally conductive adhesive composition within the above range, an advantageous balance between thermal conductivity and adhesion can be achieved. Furthermore, due to the thermal conductivity in the above range, the adhesive composition is particularly suitable for use in the assembly of energy storage devices, such as automotive batteries.
[0065] In general, the thermal conductivity of a thermally conductive adhesive is achieved at the expense of the adhesive's adhesive and mechanical properties. It has been surprisingly found that the polyurethane-based thermally conductive adhesive of the present invention not only exhibits excellent thermal conductivity, but also has advantageous mechanical properties. In some preferred embodiments, the cured polyurethane-based adhesive of the present invention exhibits a lap shear strength (LSS) on untreated aluminum plate of 7.8 MPa or more, preferably 9.0 MPa or more, more preferably 11.0 MPa or more, as measured by ASTM D1002-2010, and a peel strength on aluminum-plastic film of 600 gf / cm or more, preferably 650 gf / cm or more, preferably 700 gf / cm or more, more preferably 900 gf / cm or more, as measured at 23°C by ASTM D903-1998. It has been surprisingly found that the formulation of the cured adhesive composition within the claimed ranges allows for a balance of different adhesive properties to different materials.
[0066] The cured polyurethane-based thermally conductive adhesive composition is particularly suitable for use in the assembly of energy storage devices, such as batteries. Therefore, it is important that the cured polyurethane-based thermally conductive adhesive composition does not exhibit significant electrical conductivity. On the other hand, it is preferable that the cured polyurethane-based thermally conductive adhesive composition exhibits good flame retardancy.
[0067] Method for preparing two-component polyurethane-based thermally conductive adhesive composition Composition A: 1. The raw materials including polyol, crosslinker and thermal conductive filler are charged into the mixer, heated to 85℃, and stirred under vacuum for 2 hours, and the moisture content is controlled below 500ppm; 2.Cool down to 40℃, then add additives and color paste if any, and stir under vacuum for 2 hours, controlling the equipment temperature below 40℃; 3. Discharge the product and measure its viscosity according to ASTM D2196-2015 using an Anton Paar Rheometer with a PP25 spindle at a shear rate of 1 s -1 Tested with.
[0068] (Poly)isocyanate prepolymer: 1. Charge the hydroxyl-terminated polybutadiene into the mixer, heat to 85℃, and stir under vacuum for 2 hours, controlling the moisture content below 1500ppm; 2. Cool to 30°C, continue stirring, add aromatic isocyanate to the mixer, increase temperature to 80°C and stir under nitrogen for 2 hours; 3. Cool to 40°C and continue stirring under vacuum while cooling; 4. The product is discharged and the NCO content is determined by the Spiegelberger method.
[0069] Composition B: 1. The produced (poly)isocyanate prepolymer, isocyanate and thermally conductive filler are charged into a mixer and stirred under vacuum for 2 hours, and the equipment temperature is controlled below 40°C; 2. Discharge the product and measure the viscosity and NCO content.
[0070] Mixing and curing The product is processed from universal cartridges using manual application tools (hand, pneumatic or battery-powered guns). Only cartridge pistols with piston rods are used. Before screwing into the static mixer, a small amount of material must be pushed out so that both components pass at the same time. After mixing, the adhesive is ready for use and must be processed within the given pot life, since the viscosity increases as curing begins. The pot life depends on the temperature and the amount mixed. To prevent the adhesive parts from shifting, it is recommended that they are always fixed during the curing process. The static mixer can be left installed during out-of-service periods, and if the product is to be used further, it is simply removed and a new one installed.
[0071] The product can be applied by using a suitable two-component system with a high-pressure pump, preferably a volume-controlled dispenser. The two components are mixed by using a static or dynamic mixing system. The given mix ratio should not deviate from the set value by more than ±5%. Before screwing the static mixer, a small amount of material must be extruded so that both components pass simultaneously. To ensure proper mixing, about the first 10-20 cm of the adhesive bead is discarded. After mixing, the material must be applied within the given pot life. If application is interrupted, the mixture must be purged from the mixer. If the interruption is significant, purging must be done by using only one component to stop the two-component reaction. When application is resumed, the mixing system must be purged again until all unmixed material has been washed out of the nozzle. Preferably, the adhesive is applied to the parts to be bonded immediately after mixing. The material is applied on one side and the parts should be directly assembled.
[0072] List of embodiments 1.a) Component (A) comprising a polyhydroxy compound and a crosslinker, wherein the polyhydroxy compound comprises a polyether polyol having a weight average molecular weight of 300 to 1200 and a hydroxy functionality of 2; b) component (B) comprising an isocyanate-containing compound and a (poly)isocyanate prepolymer having active isocyanate groups prepared by reacting a hydroxyl-terminated polybutadiene with an excess amount of an aromatic isocyanate, wherein the molar ratio of the OH groups of the hydroxyl-terminated polybutadiene to the NCO groups of the aromatic isocyanate is 0.23-0.32; A two-component polyurethane-based thermally conductive adhesive composition comprising: A two-component polyurethane-based thermally conductive adhesive composition, wherein component (A) and / or component (B) contain a thermally conductive filler, the content of the thermally conductive filler being 82.5 to 85.0% by weight based on the total amount of the composition, and components (B) and (A) are present in a ratio of NCO groups of the isocyanate-containing compound and (poly)isocyanate prepolymer to OH groups of the polyhydroxy compound of 0.8 to 1.6.
[0073] 2. The composition according to embodiment 1, wherein components (B) and (A) are present in a ratio of NCO groups of the isocyanate-containing compound and the (poly)isocyanate prepolymer to OH groups of the polyhydroxy compound of 0.9 to 1.2.
[0074] 3. The composition according to any one of the previous embodiments, wherein the hydroxyl-terminated polybutadiene having a polybutadiene structure is solely a 1,2-vinyl structure or a 1,4-trans structure, or a mixture of a 1,2-vinyl structure and a 1,4-trans structure, or a 1,2-vinyl structure, a 1,4-trans structure and a 1,4-cis structure, or a mixture of a 1,4-trans structure and a 1,4-cis structure.
[0075] 4. The composition of any one of the previous embodiments, wherein the hydroxyl-terminated polybutadiene is a linear, non-hydrogenated, hydroxyl-terminated polybutadiene that is liquid at 25° C.
[0076] 5. The composition of any one of the previous embodiments, wherein the hydroxyl-terminated polybutadiene is a hydroxyl-terminated polybutadiene having a number average molecular weight in the range of 1000 to 5000 g / mol, and / or an average hydroxy (OH) functionality in the range of 1.7 to 3.5.
[0077] 6. The composition of any one of the previous embodiments, wherein the hydroxyl-terminated polybutadiene is a liquid hydroxyl-terminated polybutadiene having a number average molecular weight (Mn) in the range of 1200 to 4500 g / mol and / or an average hydroxy (OH) functionality in the range of 1.9 to 2.4.
[0078] 7. The composition of any one of the previous embodiments, wherein the hydroxyl-terminated polybutadiene is reacted with an access amount of aromatic isocyanate in an amount of 3.00 to 5.50 weight percent, based on the total weight of the two-part polyurethane-based thermally conductive adhesive composition.
[0079] 8. The composition of any one of the previous embodiments, wherein the hydroxyl-terminated polybutadiene is reacted with an access amount of aromatic isocyanate in an amount of 3.29 to 4.69 weight percent, based on the total weight of the two-part polyurethane-based thermally conductive adhesive composition.
[0080] 9. The composition of any one of the previous embodiments, wherein the aromatic isocyanate is selected from the group consisting of TDI, 4,4'-diphenylmethane diisocyanate (MDI), carbodiimide-modified 4,4'-diphenylmethane diisocyanate (CMDI), and combinations thereof.
[0081] 10. The composition according to any one of the previous aspects, wherein the (poly)isocyanate prepolymer having active isocyanate groups is prepared by reacting a hydroxyl-terminated polybutadiene with an excess of an aromatic isocyanate, and the molar ratio of OH groups of the hydroxyl-terminated polybutadiene to NCO groups of the aromatic isocyanate is from 0.235 to 0.261.
[0082] 11. The composition of any one of the previous embodiments, wherein the crosslinker has a weight average molecular weight of 400-500 and a hydroxy functionality of 3.
[0083] 12. A cured product of the two-component polyurethane-based thermally conductive adhesive composition according to any one of the preceding aspects.
[0084] 13. The cured product of embodiment 12, wherein the cured product has a peel strength of 600 gf / cm or greater when subjected to ASTM D903-1998, a lap shear strength of 7.8 MPa or greater when subjected to ASTM D1002-2010, and a thermal conductivity of 1.98 W / (m·K) or greater when subjected to ISO 22007-2-2015.
[0085] 14. An article comprising two different substrates, the article comprising the cured product of any one of embodiments 12 or 13 as a thermally conductive adhesive for bonding the substrates.
[0086] 15. Use of the cured product of any one of embodiments 12 or 13 as a thermally conductive adhesive for bonding substrates.
[0087] 16. Use of the claimed embodiment 15 in the manufacture of batteries in the automotive industry. EXAMPLES
[0088] Working Example: The present invention will be described and explained in more detail with reference to the following examples. The examples are intended to help those skilled in the art to better understand and practice the present invention, but are not intended to limit the scope of the present invention. All numerical values in the examples are by weight unless otherwise specified.
[0089] Example 1 (E1) <Preparation of Component A> 1. 2.45g of polyol VORANOL WD 2104 Polyol (Fn=2, Mw=400), 6g of crosslinker VORANOL CP 450 Polyol (glycerin propoxylated polyether triol, Fn=3, Mw=450), 12g of alumina NSM-2, 41.16g of alumina QYH40, 27.5g of alumina QY5-1, 8.39g of aluminum hydroxide FA-051, and 1.8g of molecular sieve powder 3A (manufactured by Shanghai BOJ Molecular Sieve Co. Ltd.) were added to a PC Laborsystem Planetary Mixer (LPV 3 LA 2G-1430C-15 type), heated to 85°C, stirred under vacuum at 350 RPM for 2 hours, and the moisture content was controlled to 500 ppm or less; 2. The mixture of step 1 was cooled to 40°C, and 0.5g of fumed silica AEROSIL R 202 (from EVONIK Company), 0.1g of DISPERBYK-145 (from BYK Company) and 0.1g of blue color paste 177-5O2295 (from BOMEX Company) were added, and stirred under vacuum at 350 RPM for 2 hours, and the system temperature was controlled below 40°C; 3. The product of step 2 was discharged.
[0090] <Preparation of prepolymer> 1. 50 g of hydroxyl-terminated polybutadiene Poly bd R-15HT (Idemitsu Kosan, Mn=1200, Fn=2.4) was placed in a PC Laborsystem Planetary mixer (LPV 3 LA 2G-1430C-15 model), heated to 85°C, and stirred at 350 RPM under vacuum for 2 hours to control the moisture content to 1500 ppm or less; 2. The mixture from step 1 was cooled to 30°C, stirring was continued, 50g of isocyanate DESMODUR CD-C was added to the mixer, the temperature was raised to 80°C and stirred for 2 hours under nitrogen atmosphere; 3. The product of step 2 was cooled to 40°C and kept stirring at 350 RPM under vacuum during cooling; 4. The product was discharged.
[0091] <Preparation of Component B> 1. 3 g of isocyanate DESMODUR CD-C, 16 g of prepolymer PP3, 64.96 g of alumina QYH40, 12.04 g of alumina QY5-1, 0.88 g of fumed silica AEROSIL R 202 (manufactured by EVONIK Company) and 3.12 g of plasticizer DISFLAMOLL DPK (manufactured by LANXESS Company) were placed in a PC Laborsystem Planetary mixer (model LPV 3 LA 2G-1430C-15) and stirred at 350 rpm under vacuum for 2 hours, and the temperature of the equipment was controlled below 40°C; 2. The product was discharged.
[0092] <Mixed> Component A and component B were mixed in a volume ratio of 1:1 by a static mixer. The mixed material was applied to a substrate and directly assembled with another substrate. Considering that the densities of components A and B were 2.89 g / mL and 2.43 g / mL, respectively, in Example 1, the weight ratio of components A and B was 2.89:2.43.
[0093] Examples 2 to 8 (E2 to E8) and Comparative Examples 1 to 3 (CE1 to CE3) Adhesive compositions E2-E8 and CE1-CE3 were prepared with reference to Example 1. Further details are provided in the Results section below.
[0094] Comparative Example CE4 CE4 is a comparative example of E1. Since no prepolymer is used, there is no prepolymer preparation step; isocyanate DESMODUR CD-C and hydroxyl-terminated polybutadiene Poly bd R-15HT (Idemitsu Kosan, Mn=1200, Fn=2.4) were added separately to parts A and B in step 1, and the rest of the preparation steps were the same as E1. Further details are shown in Table 2.
[0095] The prepared samples were subjected to various tests.
[0096] Test Method <Peel strength> The peel strength was tested according to ASTM D903-1998. The two substrates were an aluminum plate (25mm wide, 100mm long) and an aluminum plastic film (25mm wide, 200mm long). Before use, the substrate surfaces needed to be cleaned of dust and oil; the test specimens were bonded together with adhesive, with the adhesive area controlled to about 25×80mm and the thickness controlled to about 0.3mm.
[0097] The specimens were aged for 7 days in a controlled environment room (23°C, 50% relative humidity) and then tested for peel strength using a Zwick tensile tester at a travel speed of 300 mm / min. Each test was repeated three times and the average value of gf / cm was calculated.
[0098] Peel strength results are recorded and ranked as follows: -Fail: Less than 600gf / cm; -Pass: 600gf / cm or more; -Good: 700gf / cm or more; -Excellent: 900gf / cm or more.
[0099] <Lap shear strength> The overlap shear strength was tested according to ASTM D1002-2010. The aluminum sample strips (25 mm wide, 100 mm long) were wiped with isopropanol three times before use. Two aluminum sample strips were glued together with adhesive to control the adhesive area to about 25 x 25 mm and the thickness to about 0.3 mm.
[0100] Lap shear strength results are recorded and rated as follows: -Failed: less than 7.80MPa; -Pass: 7.80MPa or higher; -Good: 9.0MPa or more; -Excellent: 11.0MPa or higher
[0101] The specimens were aged for 7 days in a controlled environment room (23°C, 50% relative humidity) and then tested for overlap shear strength using a Zwick tensile testing machine at a travel speed of 12.7 mm / min. Each test was repeated three times and the average value in MPa was calculated.
[0102] <Thermal conductivity> Thermal conductivity was tested according to ISO 22007-2-2015. The specimens were aged for 7 days in a controlled environment room (23°C, 50% relative humidity) and then measured at room temperature (25°C) using a Hot Disk TPS 3500 tester. Each test was repeated three times and the average value in W / (m K) was calculated.
[0103] Thermal conductivity results are recorded and ranked as follows: -Fail: less than 1.98 W / (m K); -Pass: 1.98W / (m·K) or more; -Good: 2.0W / (m·K) or more; -Excellent: 2.1W / (m·K) or more.
[0104] result Table 1 shows the preparation of prepolymers with different OH:NCO molar ratios.
[0105] [Table 1]
[0106] Table 2 shows the formulations of Examples 1-3 (E1-E3) and Comparative Example 1 (CE1 and CE4) with different prepolymers or without prepolymer.
[0107] [Table 2]
[0108] From Tables 1 and 2 above, it can be seen that good adhesive properties and good thermal conductivity can be achieved by using a (poly)isocyanate prepolymer having active isocyanate groups prepared by reacting hydroxyl-terminated polybutadiene with an excess of aromatic isocyanate, and the molar ratio of OH groups of the hydroxyl-terminated polybutadiene to NCO groups of the aromatic isocyanate is within the claimed range. It has been unexpectedly found that the thermally conductive adhesive exhibits a combination of desired properties, especially excellent adhesive properties, between two different surfaces at such a high loading ratio of thermally conductive filler.
[0109] Table 3 shows the formulations of Examples 4-8 (E4-E8) and Comparative Examples 2-3 (CE2-CE3).
[0110] [Table 3]
[0111] The more the amount of thermally conductive filler, the higher the thermal conductivity. From the above table, it can be seen that the amount of thermally conductive filler has a large effect on the thermal conductivity, and the amount of thermally conductive filler also affects the adhesive properties, especially the lap shear strength. On the other hand, the molar ratio of free isocyanate and NCO groups on the prepolymer to hydroxyl groups on the polyol in the formula of the two-part adhesive composition also affects the adhesive properties, so in order to balance all the properties, a suitable molar ratio of NCO / OH and the amount of thermally conductive filler in the formula of the two-part adhesive composition are required.
Claims
1. a) component (A) comprising a polyhydroxy compound and a crosslinker, the polyhydroxy compound comprising a polyether polyol having a weight average molecular weight of 300 to 1200 and a hydroxy functionality of 2; b) component (B) comprising an isocyanate-containing compound and a (poly)isocyanate prepolymer having active isocyanate groups prepared by reacting a hydroxyl-terminated polybutadiene with an excess of an aromatic isocyanate, wherein the molar ratio of the OH groups of the hydroxyl-terminated polybutadiene to the NCO groups of the aromatic isocyanate is 0.23 to 0.32; A two-component polyurethane-based thermally conductive adhesive composition comprising: The component (A) and / or the component (B) contain a thermally conductive filler, the content of the thermally conductive filler being 82.5 to 85.0% by weight based on the total amount of the composition, and the component (B) and the component (A) are present in a ratio of NCO groups of the isocyanate-containing compound and (poly)isocyanate prepolymer to OH groups of the polyhydroxy compound of 0.8 to 1.
6.
2. 2. The composition of claim 1, wherein said component (B) and said component (A) are present in a ratio of NCO groups of said isocyanate-containing compound and said (poly)isocyanate prepolymer to OH groups of said polyhydroxy compound of 0.9 to 1.
2.
3. The composition of claim 1, wherein the hydroxyl-terminated polybutadiene having a polybutadiene structure has a 1,2-vinyl structure or a 1,4-trans structure alone, or a mixture of a 1,2-vinyl structure and a 1,4-trans structure, a 1,2-vinyl structure, a 1,4-trans structure and a 1,4-cis structure, or a mixture of a 1,4-trans structure and a 1,4-cis structure.
4. 2. The composition of claim 1, wherein the hydroxyl terminated polybutadiene is a linear, non-hydrogenated, hydroxyl terminated polybutadiene that is liquid at 25°C.
5. 2. The composition of claim 1, wherein the hydroxyl-terminated polybutadiene is a hydroxyl-terminated polybutadiene having a number average molecular weight in the range of 1000 to 5000 g / mol and / or an average hydroxy (OH) functionality in the range of 1.7 to 3.
5.
6. 2. The composition of claim 1, wherein the hydroxyl terminated polybutadiene is a liquid hydroxyl terminated polybutadiene having a number average molecular weight (Mn) in the range of 1200 to 4500 g / mol, and / or an average hydroxy (OH) functionality in the range of 1.9 to 2.
4.
7. The composition of claim 1, wherein the hydroxyl terminated polybutadiene is reacted with an access amount of the aromatic isocyanate in an amount of 3.00 to 5.50 weight percent based on the total weight of the two-part polyurethane-based thermally conductive adhesive composition.
8. 2. The composition of claim 1, wherein the hydroxyl terminated polybutadiene is reacted with the aromatic isocyanate in an accessible amount of 3.29 to 4.69 weight percent, based on the total weight of the two-part polyurethane-based thermally conductive adhesive composition.
9. 2. The composition of claim 1, wherein the aromatic isocyanate is selected from the group consisting of TDI, 4,4'-diphenylmethane diisocyanate (MDI), carbodiimide-modified 4,4'-diphenylmethane diisocyanate (CMDI), and combinations thereof.
10. 2. The composition of claim 1, wherein the (poly)isocyanate prepolymer having active isocyanate groups is prepared by reacting a hydroxyl-terminated polybutadiene with an excess of the aromatic isocyanate, and the molar ratio of OH groups of the hydroxyl-terminated polybutadiene to NCO groups of the aromatic isocyanate is from 0.235 to 0.
261.
11. The composition of claim 1, wherein the crosslinker has a weight average molecular weight of 400 to 500 and a hydroxy functionality of 3.
12. A cured product of the two-component polyurethane adhesive composition according to any one of claims 1 to 11.
13. The cured product according to claim 12, wherein the cured product has a peel strength of 600 gf / cm or more when measured in accordance with ASTM D903-1998, a lap shear strength of 7.8 MPa or more when measured in accordance with ASTM D1002-2010, and a thermal conductivity of 1.98 W / (m K) or more when measured in accordance with ISO 22007-2-2015.
14. 13. An article comprising two different substrates, the article comprising the cured product of claim 12 as a thermally conductive adhesive for bonding the substrates.
15. 13. Use of the cured product of claim 12 as a thermally conductive adhesive for bonding substrates.
16. 16. Use of claim 15 in the manufacture of batteries in the automotive industry.
Citation Information
Patent Citations
Low-viscosity high-thermal-conductivity two-component polyurethane adhesive and preparation method and application thereof
CN111534268A
Two-component polyurethane adhesive and application thereof
CN111808570A
Polyurethane-based binder systems
JP2020521022A
resin composition
JP2020533440A
Two component polyurethane composition
US20190322914A1